How much do the characteristics of independent directors and supervisory board members affect firm performance in China? - Hongmei Xu (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2013)
This paper investigates and compares the characteristics of independent directors and supervisory board members in Chinese listed firms. The occupational backgrounds of independent directors and supervisory board members in listed firms are very different. Besides, different firms have different preferences in employing independent directors and supervisory board members according to their demands. Moreover, the empirical results show that characteristics of independent directors and supervisory board members have no clear relationship with firm performance. No matter their professional backgrounds or age, the independent directors and supervisory board members do not have the authority to affect the decision making process of management. Thus they cannot really contribute to firm performance. – – Die vorliegende Studie untersucht und vergleicht die Merkmale von unabhängigen Direktoren und Aufsichtsratsmitgliedern in börsennotierten chinesischen Unternehmen. Der berufliche Hintergrund der unabhängigen Vorstands- und Aufsichtsratsmitglieder in börsennotierten Unternehmen ist sehr verschieden. Verschiedene Unternehmen haben auch unterschiedliche Präferenzen bei der Beschäftigung von unabhängigen Direktoren und Aufsichtsratsmitgliedern je nach ihren Anforderungen. Außerdem zeigen die empirischen Ergebnisse, dass die Merkmale von unabhängigen Vorstands- und den Aufsichtsratsmitgliedern in keinem klarem Zusammenhang zum Unternehmenserfolg stehen. Unabhängig von ihrem professionellem Hintergrund und Alter haben weder die unabhängige Direktoren noch die Aufsichtsratsmitglieder ausreichenden Einfluss auf die Entscheidungsprozesse des Managements. Folglich können sie nicht wirklich zum Unternehmenserfolg beitragen.
Keywords: G30; G34; M51; O16; P31; 650